Homem não chora: o abuso sexual contra meninos - Carvalho, Fabiana Aparecida de (2015)
The present study has the title: "Men don't cry: the sexual abuse against boys". In Brazil, in 2012, it was registered 10425 cases of sexual abuse against children and youngsters, where 8677 were against girls. In the majority of cases the perpretator of the abuse is a male and from the trust circle of the child. The diference between male victims and female victims is very obvious and the perpetrators - in their majority - are men. Why do we study boys as victims? The invisibility of boys in the context of sexual victimisation called our attention and became the focus of this research. Some cultural factors corroborate for the boys' sexual victimisation concealing, such as: the understanding of the fact with naturality comprehending the event as "man's thing"; the heritage of resistance and male virility, by mean of which hide what happened, by fear of social reprisal and of futures questioning about the victim's masculinity. The study's objective consisted in investigate the consequences of the sexual abuse for the boy and analise the repercussion of the sexual violence against the man/boy in the familiar convivence and communitarian. Of qualitative nature, we performed profound interviews with three boys and a man that experienced sexual abuse, two mothers and one victimised boy's carer. The research's results revealed different meanings atributed to the suffered sexual abuse, according to trajectory and the experiences of each subject. The homossexuality fear developed from sexual abuse was present in some interviewed's speech, as well as the reproduction of the abuse. Several historical advances through the action of different social movements have gained a solid agenda about the topic in general agenda of public policy. However, the cultural transformation that can alter the rigidity of genres is still a challenge to be pursued, as well as advance our understanding of sexuality in its human dimension and authorization to talk about it, without configurating other violence for this